Kemampuan Pemecahan Masalah Matematika ditinjau dari Gaya Belajar Siswa Kelas VIII SMP Negeri 6 Mataram Tahun Pelajaran 2020/2021 - Baiq Yuspita Halilianti; Sripatmi Sripatmi; Syahrul Azmi; Nyoman Sridana (Griya Journal of Mathematics Education and Application, 2022)
This study aimed to describe the mathematical problem solving ability of eighth grade students of SMPN 6 Mataram in terms of visual, auditory and kinesthetic student learning styles. In this study, the writer used design of qualitative-descriptive with a quantitative approach. The instruments used are student learning style questionnaires, problem-solving ability test questions, and interview guidelines. The results of filling out the questionnaire via google form, there are 191 eighth grade students who fill out a questionnaire with details of visual, auditory, and kinesthetic learning styles sequentially are 84, 70, 37. Afterwards, with purposive sampling technique, one class is selected to work on the test questions and 2 students from each learning style to be interviewed. The results of this study are students with visual learning styles have higher problem solving abilities than students with auditory and kinesthetic learning styles at each stage of problem solving. Students with visual learning styles are very good at understanding problems, good at planning, sufficient in the stage of carrying out solutions, and less in the stage of looking back. Students with an auditory learning style are good at understanding problems, sufficient at the stage of planning and implementing solutions, but very less in the stage of looking back. Meanwhile, students with a kinesthetic learning style are very good at understanding the problem, sufficient at the stage of implementing the plan, but very less at the stage of making plans and looking back.